Preserving Spiritual Rights through Halal Certification for MSME Products: Voluntary vs. Mandatory - Disemadi, Hari Sutra; Putri, Arya Salsabila Auliana (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
Halal certification of products is a manifestation of legal protection for Muslim consumers related to efforts to safeguard their spirituality. As a predominantly Muslim country, Indonesia is expected to protect its citizens by fulfilling their fundamental rights. Furthermore, the state strives to develop the domestic halal food industry to promote its growth. Following the enactment of Law Number 33 of 2014 concerning Halal Products Assurance, every business entity that sells essential goods utilized by the public is required to have halal certificate and label, including micro, small, and medium enterprises (MSME). This normative legal or doctrinal research is a qualitative examination that analyzes legal materials related to the protection of spiritual rights through halal certification. The results show the role of the government in ensuring the safety, comfort, and smoothness of Muslim consumers in practicing their religious teachings. Obligation imposed on every business entity to obtain certification creates legal protection for users of these products. Certification registration by business entities, including MSME, provides legal certainty for the protection of consumers' spiritual rights.